Inflammatory biomarker detection in saliva samples by printed graphene immunosensors - D. Vurro; L. Pasquardini; M. Borriello; R. Foresti; M. Barra; M. Sidoli; D. Pontiroli; L. Fornasini; L. Aversa; R. Verucchi; P. D'Angelo; G. Tarabella (Sensors and Actuators Reports)
Herein, we present the design and fabrication of a portable biochemical sensor based on the Screen Printed Electrode (SPE) concept and applied for detecting interleukin-6 (IL-6), a key player in the complex process of inflammation, in real human saliva. The sensing mechanism relies on the antigen-antibody binding between the IL-6 molecule and its antibody immobilized over a surface of a Thermally Exfoliated Graphene Oxide (TEGO) layer. TEGO, deposited by Aerosol Jet Printing (AJP), provides advantages in terms of a time/cost consumingfast, easy and efficient biofunctionalization. The biosensor shows a dynamic range comprising IL-6 concentrations falling within the normal IL-6 levels in saliva. An extensive analysis of device performance, focused on the assessment of the sensor Limit of Detection (LoD) by two modes (i.e. from the lin-log calibration curve and from blank measurements), provides a best value of about 1 × 10−2 pg/ml of IL-6 in saliva. Our work aims at providing a contribution toward applications in real environment, going beyond a proof of concept or prototyping at lab scale. Hence, the characterization of the sensor was finalized to find a reliable device-to-device reproducibility and calibration through the introduction of a measurement protocol based on comparative measurements between saliva samples without (blank) and with IL-6 spiked in it, in place of the standard addition method used in daily laboratory practice. Device-to-device reproducibility has been accordingly tested by acquiring multiple experimental points along the calibration curve using different individual devices for each point.